Prarancangan Pabrik Trisodium Fosfat Dari Asam Fosfat, Sodium Karbonat Dan Sodium Hidroksida Dengan Kapasitas 45.000 Ton/Tahun - Hadaina, Faza, Ir. Nur Hidayati, M.T., Ph.D, Hamid Abdillah, S.T., M.T (2017)
Trisodium phosphate primarily is used for production of detergent and cleaning soap industry. Trisodium phosphate is imported with no production in Indonesia. Hence, it will be beneficial to build a Trisodium Phosphate Plant with duction capacity of 45.000 ton/years to meet domestic demand and to be exported. This plant will be operated for 330 days per year and will be established in Gresik, East Java in 2022. Trisodium phosphate is formed from phosphoric acid, sodium carbonate, and sodium hydroxide in a Continuous Stirred Tank Reactor (CSTR) with operating temperature of 90oC and essure at 1 atm. There are several stages of the Trisodium hosphate production. Those are oductformation,evaporation,crystallization, and drying process. The process would need 2.953,99 kg/hour phosphoric acid, 1.612,97 kg/hour sodium carbonate, and 606,06 kg/hour sodium hydroxide. The proposed plant would include the utility unit that need fresh water for 87.033,44 kg/hour from the closest river, saturated steam for .307,79ukg/hour, compressed air for 150 m3/hour, electrical supply for 729,38 kW from PLN and 1000 kW set of generator as a reserved electricity, and fuel oils for 7.826,22 liter per day. The company type would be a limited liability company. The amount of employee is 170 people. Percent return on investment (ROI) before tax is 25,69% and after tax is 17,98%. Pay out time (POT) before tax is 2,80 years and after tax is 3,57 years. Break even point (BEP) is 42,02%, shut down point (SDP) is 16,07%, internal rate of return (IRR) based on discounted cash flow (DCF) is 24,22%. From this analysis, it can be conclude that this plant feasible to set up.